Gangguan Kognitif Pasca Stroke - Edi Prasetyo (Lembaga Pengembangan Kinerja Dosen, 2026)
Cognitive impairment is a common post-stroke consequence that has a significant impact on the patient's daily functioning and quality of life. This article presents a literature review of six recent studies, consisting of three multicenter cohort studies, two systematic review studies and meta-analysis, and one cross-sectional study, to examine the characteristics and implications of post-stroke cognitive decline. The findings show that post-stroke cognitive impairment is strongly correlated with activity limitations in both the early and long-term phases, as well as restrictions on participation in community life. In addition, cognitive impairment contributes to a higher functional load and decreases the patient's social adaptability. The various cognitive assessment instruments used in these studies emphasized the importance of early cognitive evaluation to detect cognitive impairment, predict functional outcomes, and design targeted rehabilitation interventions. The clinical implications of this review emphasize the need to integrate cognitive assessment into stroke care standards to improve rehabilitation effectiveness, support patient self-recovery, and improve long-term quality of life.